Experimental study of flank wear in high speed turning of stainless steel AISI 304 - Al Hazza, Muataz Hazza Faizi; Md Yusof, Nabilah; -, Nur Amirah Najwa; -, Mohd Eikhwan; -, Mohamad Khazairul; Taha, Assem Hatem (Design for Scientific Renaissance, 2013)
One of the main approaches to reduce the machining time in metal cutting is High Speed Turning (HST). HST increases the material removal rate and then decreases the total machining time. However, in these speeds the flank wear progress will also increase. The aim of this paper is to study experimentally the influence of higher cutting speed on flank wear length when machining AISI 304 as work piece material. This steel is machined by a coated carbide tool. The experiments were planned and implemented using Box Behnken Design (BBD) of Response Surface Methodology (RSM) with three input factors: cutting speed, feeding speed and depth of cut. The experimental results showed that cutting speed is the most effective factor on the flank wear.